Влияние граничных условий на активное демпфирование колебаний пластины при использовании показателей сенсоров - Карнаухова, Т.В. (Прикладная механика, 2010)
Basing on new approach, an effect of boundary conditions on effectiveness of
active damping of forced resonance vibrations of a viscoelastic orthotropic plate is studied. The
cases of hinged and rigid fixing the plate ends as well as the case of mixed boundary conditions
are considered. The problems are solving by the Bubnov – Galerkin method. For each of mentioned
cases, the formulas for potential differences are obtained, which should be applied to the actuator
for damping the first mode of vibrations. It is shown that boundary conditions, dissipative
properties of the material and size of sensor and actuator effect essentially on effectiveness of active damping of the plate vibrations. На основі запропонованого автором нового підходу досліджено вплив змішаних
механічних граничних умов на ефективність активного демпфування вимушених резонансних коливань
термов’язкопружних ортотропних пластин. Задачу розв’язано методом Бубнова – Гальоркіна.
Одержано формули для різниці потенціалів, яку потрібно підвести до актуатора для демпфування першої
моди коливань. Показано, что механічні граничні умови, дисипативні властивості матеріалів і
розміри сенсорів та актуаторів суттєво впливають на ефективність активного демпфування коливань
пластин.